2014
DOI: 10.1007/s00221-014-3970-5
|View full text |Cite
|
Sign up to set email alerts
|

Speed of perceptual grouping in acquired brain injury

Abstract: Evidence exists that damage to white matter connections may contribute to reduced speed of information processing in traumatic brain injury and stroke. Damage to such axonal projections suggests a particular vulnerability to functions requiring integration across cortical sites. To test this prediction, measurements were made of perceptual grouping, which requires integration of stimulus components. A group of traumatic brain injury and cerebral vascular accident patients and a group of age-matched healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The results from this study indicating that children with TBI have visual integration deficits are in line with the scarcely available literature. One study showed that a small sample of adult patients with acquired brain injury ( n = 13) had impaired spatial grouping of visual stimuli, thought to be caused by reduced integration of information in the visual cortex after axonal disruption [ 32 ]. A functional magnetic resonance imaging study further showed that an increased load on the integration of visual features in an attention task was associated with impaired task performance in a small sample of patients with diffuse axonal injury after TBI (n = 7) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study indicating that children with TBI have visual integration deficits are in line with the scarcely available literature. One study showed that a small sample of adult patients with acquired brain injury ( n = 13) had impaired spatial grouping of visual stimuli, thought to be caused by reduced integration of information in the visual cortex after axonal disruption [ 32 ]. A functional magnetic resonance imaging study further showed that an increased load on the integration of visual features in an attention task was associated with impaired task performance in a small sample of patients with diffuse axonal injury after TBI (n = 7) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%